EVALUASI KEKUATAN STRUKTUR GEDUNG H UNIVERSITAS DIAN NUSWANTORO SEMARANG - Nur Fahria R.D.; Ita Puji Lestari; Himawan Indarto; Indrastono Dwi Atmanto (Jurnal Karya Teknik Sipil, 2016)
Poor supervision in the project execution can cause a mediocre performance of construction quality, including concrete quality. Structural Strength Evaluation on the seven stories building, building H of Dian Nuswantoro University has demonstrated the impacts of poor performance of these concrete qualities. The concrete quality have been designed by K250, ,and decrease to K150 because of that poor supervision from level 1 to 3. The function of first three levels are supporting four stories above by concrete quality K300.The impact evaluation of different concrete quality on the building H is undertaken by comparative assessment throughout three SNI, they are SNI 03-1726-2012, SNI 03-2847-2013, and SNI 1727-2013.Structural evaluation is undertaken by three dimensional simulation method from the field data information. Based upon the structural simulation, therefore the main structure need a strengthening to support the service load of the building H. The result of structural analysis due to the standard found that some of beam elements need a strengthening by enlarging section area and increasing reinforcement ratio of the column.